Some Basic Considerations in Organization Planning - Efferson, Carlos A. (Academy of Management Journal, 1959)
Analyzes basic problems and approaches in organization planning, using Kaiser Aluminum Reason for starting an organization planning program; How the organization planning function is established at Kaiser Aluminum & Chemical Corp.